Glyphosate Applications, Glyphosate Resistant Corn, and Tillage on Nitrification Rates and Distribution of Nitrifying Microbial Communities. Issue 6 (22nd November 2017) - Jenkins, Michael; Locke, Martin; Reddy, Krishna; McChesney, Daniel S.; Steinriede, R.
Abstract : Core Ideas: The herbicide glyphosate can affect nitrification rates. Archaeal nitrifiers were dominant in the rhizosphere. In bulk soil, bacterial and archaeal nitrifiers were evenly distributed. We tested the null hypothesis that nitrification and the distribution of archaeal and bacterial nitrifying communities would not be impacted by long‐term applications of the herbicide, glyphosate, to glyphosate‐resistant (GR) and non‐glyphosate‐resistant corn (nonGR) under conventional tillage (CT) and reduced tillage (RT) systems. Bulk and rhizosphere soil nitrification potential rates and quantification of amo A genes of archaeal (AOA) and bacterial (AOB) communities were undertaken. In 2013, the nitrification rate of nonGR corn with no glyphosate application treatment associated with bulk and rhizosphere soils under RT displayed greater ( P < 0.05) nitrification rates than GR corn with glyphosate applications. In 2014, the nitrification rate of the rhizosphere soil under RT in GR corn with no glyphosate application treatment was greater ( P < 0.05) than other rhizosphere soil treatments. Ratios between archaeal and bacterial amo A genes indicated distinct dominance of AOA communities in the rhizosphere soil. The ratios between AOA and AOB amo A genes in bulk soil were more balanced. Regression analyses indicated more significant correlations between nitrification potential determinations and bulk soil nutrients ratios, nutrient acquisition ratios, and microbial communities than between analogous rhizosphere soil characteristics. Compared to non‐glyphosate treatments, glyphosate applications appeared to disrupt rhizosphere nutrient, exoenzymatic, and microbial relationships. Glyphosate applications had an inconsistent inhibitory effect on the nitrification process. In contrast to bulk soil, rhizosphere soil nitrifying communities were most likely in competition with corn roots for ammonia‐N, and were thus dominated by more oligotrophic archaeal nitrifiers compared to bacterial nitrifiers.